Study of Extra intestinal E.coli and their resistant pattern in a tertiary care hospital of Bangladesh. - Ferdous, Jannatul; Begum, Taslima; Akter, Taslima; Mohammad Murshed, -; Jahan, Noor; Shahnaz, Sabeena (Bangladesh Journal of Medical Microbiology, 2017)
E.coli is one of the most important gram negative bacterial pathogen in human and can be subdivided into the following; (i) intestinal non-pathogenic, commensal variants (ii) Intestinal pathogenic isolates and (iii) extra intestinal pathogenic E.colior ExPEC isolates. ExPEC causes the vast majority of urinary tract infections (UTIs), is a leading cause of adult bacteremia and is the second most common cause of neonatal meningitis. The clinical specimens obtained from patients admitted in Holy Family Red Crescent Medical College Hospital (HFRCMCH) from January 2014 to December 2016. All laboratory works were performed in department of microbiology and immunology of HFRCMCH. The infection rate was maximum in urine (89%) followed by blood (5%), pus (5%) and others (1%). Most of the ExPEC were isolated from outdoor department 62.6%. ExPEC displayed higher resistance to many antibiotics like 75% resistant to Ampiciline , 55% resistant to Cotrimazole, 22% resistant to Gentamycin, 17% resistant to Nitrofurantoin, 55% resistant to Ciprofloxacin, 70% resistant to Ceftriaxone, 82% resistant to Cefalexin, 50% resistant to Azithromycin, 10% resistant to Amikacin, 48% resistant to Tetracycline, 7% resistant to Imipenem and 8% resistant to Meropenem. In conclusion, there were high resistant rate to commonly available antibiotics. It seems that appropriate and judicial use of antibiotics may help to control the evolving problem of drug resistance towards ExPEC. Bangladesh J Med Microbiol 2017; 11 (1): 10-13